Knowledgebase of potential multifaceted solutions to antimicrobial resistance. (December 2022) - Bhargav, Anasuya; Gupta, Srijanee; Seth, Surabhi; James, Sweety; Fatima, Firdaus; Chaurasia, Pratibha; Ramachandran, Srinivasan
Abstract: Antimicrobial resistance (AMR), a top threat to global health, challenges preventive and treatment strategies of infections. AMR strains of microbial pathogens arise through multiple mechanisms. The underlying "antibiotic resistance genes" (ARGs) spread through various species by lateral gene transfer thereby causing global dissemination. Human methods also augment this process through inappropriate use, non-compliance to treatment schedule, and environmental waste. Worldwide significant efforts are being invested to discover novel therapeutic solutions for tackling resistant pathogens. Diverse therapeutic strategies have evolved over recent years. In this work we have developed a comprehensive knowledgebase by collecting alternative antimicrobial therapeutic strategies from literature data. Therapeutic strategies against bacteria, virus, fungus and parasites were extracted from PubMed literature using text mining. We have used a subjective (sentimental) approach for data mining new strategies, resulting in broad coverage of novel entities and subsequently add objective data like entity name (including IUPAC), potency, and safety information. The extracted data was organized in a freely accessible web platform, KOMBAT. The KOMBAT comprises 1104 Chemical compounds, 220 of newly identified antimicrobial peptides, 42 bacteriophages, 242 phytochemicals, 106 nanocomposites, and 94 novel entities for phototherapy. Entities tested and evaluated on AMR pathogens are included. We envision that this database will be useful for developing future therapeutics against AMR pathogens. The database can be accessed through http://kombat.igib.res.in/ . Graphical Abstract: ga1 Highlights: Therapeutic strategies against bacteria, virus, fungus and parasites, extracted from PubMed literature. Subjective (sentimental) approach for data mining new strategies, resulting in broad coverage of novel entities. Objective approach for extraction of specific data like entity name (including IUPAC), potency, and safety information. Coverage of multifaceted antimicrobial therapeutics.